1986
DOI: 10.1177/073168448600500102
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Moisture Diffusion in Graphite/Epoxy Laminates

Abstract: Graphite/epoxy specimens, Fiberite T300/1034, were exposed to moist air of two different relative humidities. The environmental testing was made at 323 K in a computer controlled moisture chamber with very stable relative humidities of 70% and 98%.Specimens of special design were exposed to moist air to detect the diffusivity for diffusion along the fiber direction. Other specimens were used to measure moisture absorption caused by three-dimensional diffusion.A great difference was found between the diffusivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

1989
1989
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 9 publications
0
7
1
Order By: Relevance
“…It is reported that the rate of moisture diffusion in FRP increased with increasing temperatures. 16, 17 Blikstad 18 showed that the temperature dependence of moisture diffusion is anisotropic for fiber-reinforced composites. However, it has been noted that the equilibrium moisture content seems to be insensitive to temperatures, for example, in Zhang et al 10 and Loos and Springer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is reported that the rate of moisture diffusion in FRP increased with increasing temperatures. 16, 17 Blikstad 18 showed that the temperature dependence of moisture diffusion is anisotropic for fiber-reinforced composites. However, it has been noted that the equilibrium moisture content seems to be insensitive to temperatures, for example, in Zhang et al 10 and Loos and Springer.…”
Section: Introductionmentioning
confidence: 99%
“…The data are then fitted with different diffusion models. One-dimensional (1D) Fickian model has been commonly used to predict the moisture diffusion in fiber-reinforced composites, and some good correlations with experimental data have been reported, see, for example, Browning et al 9 and Katzman et al 26 In some studies, a general threedimensional (3D) Fickian model is used to describe the moisture diffusion in thick composite laminates, for example, Blikstad 18 and Yu and Pochiraju. 27 Blikstad et al 12 compared both 1D and 3D Fickian models and reported that a 3D solution has a better agreement with experiments.…”
Section: Introductionmentioning
confidence: 99%
“…2 To obtain the water diffusion coefficients in a material as heterogeneous as a composite, we have to consider the presence of at least three different phases: the epoxy matrix, the fibers and the epoxy matrix-fiber interface. It is well known that carbon fibers do not absorb humidity appreciably [2]; furthermore, Blikstad [3] recently in his review of the diffusion data on graphiteepoxy type composites [4], found that the diffusivities (at 50 ~ and R.H. between 70 and 98 %) along the fiber direction were about ten times larger than the diffusivities normal to the fiber directions: he suggested that these differences were in part due to diffusion, via high diffusivity paths, in the fiber-matrix interface.…”
Section: Methodsmentioning
confidence: 99%
“…Based on this, it can be hypothesized that an increase in the exposed fiber-matrix interfacial area would increase the rate of absorption of water by a PMC. 1,5 It has also been suggested that high pressure could increase this transport of water significantly accelerating the overall water uptake of the composite.…”
Section: -mentioning
confidence: 99%